M.N. Srinivas: (November 16, 1916 - November 30, 1999) - Beteille, Andre (2000)
M.N. Srinivas maintained an unshakable belief in the unique significance of sociology for understanding the world in which we live. Anthropology provided a method, the method of intensive fieldwork, but the important thing was to understand events and activities in the broader social perspective of structure and change. Srinivas was deeply interested in change, although he believed, quite rightly, that the sociologist would not be able to make much of change if he let go of the idea of social structure. - Reproduced
Keywords: Srinivas, M.N.